4‐Hydroxynonenal Regulates TNF‐α Gene Transcription Indirectly via ETS1 and microRNA‐29b in Human Adipocytes Induced From Adipose Tissue‐Derived Stromal Cells. Issue 8 (26th May 2016) - Zhang, Xi‐Mei; Guo, Lin; Huang, Xiang; Li, Qiu‐Ming; Chi, Mei‐Hua
ABSTRACT: Obesity is characterized by an accumulation of excessive body fat and can be diagnosed by a variety of measures, such as BMI. However, in some obese individuals, oxidative stress is also thought to be an important pathogenic mechanism of obesity‐associated metabolic syndrome. Oxidative stress increases the lipid peroxidation product, 4‐hydroxynonenal (4‐HNE), which is one of the most abundant and active lipid peroxides. Within the adipose tissue, adipocytes are derived from adipose tissue‐derived stromal cells (ADSCs), which play a key role in the generation and metabolism of adipose tissue. Additionally, obesity is associated with low‐grade inflammation. Specific microRNAs (miRNAs) that regulate obesity‐associated inflammation are largely dysregulated in metabolic syndrome (MS). In this study, we aim to confirm whether 4‐HNE and miRNAs play a role in the regulation of TNF‐α gene transcription. We enrolled six obese individuals who were referred to Harbin Medical University (Heilongjiang, China) and six nonobese control participants. Plasma 4‐HNE levels of the 12 subjects were determined by ELISA. Using qRT‐PCR, we measured ETS1, miR‐29b, SP1, and TNF‐α levels in subcutaneous white adipose tissue (WAT). Furthermore, we examined the relationship between ETS1 and TNF‐α using a luciferase reporter assay and a ChIP assay. Our results suggest that ETS1 promotes TNF‐α gene transcription in adipocytes. In addition, we demonstrated that 4‐HNE promotes TNF‐α gene transcription through the inhibition of the miR‐29b → SP1 → TNF‐α pathway and promotion of the ETS1 → TNF‐α pathway. Anat Rec, 299:1145–1152, 2016. © 2016 Wiley Periodicals, Inc.